2022
DOI: 10.2196/35363
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ Perspectives on an Electronic Medication Administration Record in Home Health Care: Qualitative Interview Study

Abstract: Background eHealth is considered by policy makers as a prerequisite for meeting the demands of health care from the growing proportion of older people worldwide. The expectation about what the efficiency of eHealth can bring is particularly high in the municipal home health care sector, which is facing pressure regarding resources because of, for example, earlier discharges from hospitals and a growing number of patients receiving medications and treatments at home. Common eHealth services in home … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…In fact, it can be argued that these centres engage all parties in care like the links of a chain; on the other hand, an inefficient management can break the links of the chain. According to the evidence, management,37 coordination,38 follow-up,39 supervision,40 training,41 recruiting and assembling an efficient team42 and formulating the rules and procedures43 to maintain and improve patient safety are among the main principles of home healthcare centres. Considering the above, these centres should try to drive their organisational culture towards patient safety 44…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it can be argued that these centres engage all parties in care like the links of a chain; on the other hand, an inefficient management can break the links of the chain. According to the evidence, management,37 coordination,38 follow-up,39 supervision,40 training,41 recruiting and assembling an efficient team42 and formulating the rules and procedures43 to maintain and improve patient safety are among the main principles of home healthcare centres. Considering the above, these centres should try to drive their organisational culture towards patient safety 44…”
Section: Discussionmentioning
confidence: 99%
“…While eHealth services can facilitate information transmission [26,27], they also have secondary effects that are worth acknowledging. For example, the use of eHealth can contribute to burnout and negatively influence job satisfaction for healthcare professionals [28,29] and working methods and professional roles can be changed in unexpected ways [30][31][32]. Previous research on eMAR has shown that nurses perceive that it can improve medication administration safety and efficiency [25], reduce medication errors [33] and improve documentation compliance [34].…”
Section: Introductionmentioning
confidence: 99%